Answer:
x = 1
y = -2
Explanation:
We have the system of equations:
-7*x - 8*y = 9
-4*x + 9*y = -22
To solve this type of system, we need to start by isolating one of the variables in one of the equations.
I will isolate the variable x in the first equation to get:
-7*x - 8*y = 9
-7*x = 9 + 8*y
x = (9 + 8*y)/(-7)
x = -(9 + 8*y)/7
Now we can replace this in the other equation to get:
-4*(-(9 + 8*y)/7) + 9*y = -22
And now we can solve this for y, we will get:
(4/7)*(9 + 8*y) + 9*y = -22
(4/7)*9 + y*(9 + 8*(4/7)) = -22
y*(63/7 + 32/7) = -22 - (36/7)
y*(95/7) = -(22*7/7) - (36/7)
y = (7/95)*(-(22*7/7) - (36/7)) = (-22*7 - 36)/95 = -2
y = - 2
Now we can replace this in the equation x = (9 + 8*y)/(-7) to find the value of x:
x = (9 +8*(-2))/(-7) = 1
Then the solution for the system is the pair (1, -2)
That means:
x = 1
y = -2